Metal Hydride Nanoparticles with Ultrahigh Structural Stability and Hydrogen Storage Activity Derived from Microencapsulated Nanoconfinement. Issue 24 (18th April 2017) - Zhang, Jiguang; Zhu, Yunfeng; Lin, Huaijun; Liu, Yana; Zhang, Yao; Li, Shenyang; Ma, Zhongliang; Li, Liquan
Abstract : Metal hydrides (MHs) have recently been designed for hydrogen sensors, switchable mirrors, rechargeable batteries, and other energy‐storage and conversion‐related applications. The demands of MHs, particular fast hydrogen absorption/desorption kinetics, have brought their sizes to nanoscale. However, the nanostructured MHs generally suffer from surface passivation and low aggregation‐resisting structural stability upon absorption/desorption. This study reports a novel strategy named microencapsulated nanoconfinement to realize local synthesis of nano‐MHs, which possess ultrahigh structural stability and superior desorption kinetics. Monodispersed Mg2 NiH4 single crystal nanoparticles (NPs) are in situ encapsulated on the surface of graphene sheets (GS) through facile gas–solid reactions. This well‐defined MgO coating layer with a thickness of ≈3 nm efficiently separates the NPs from each other to prevent aggregation during hydrogen absorption/desorption cycles, leading to excellent thermal and mechanical stability. More interestingly, the MgO layer shows superior gas‐selective permeability to prevent further oxidation of Mg2 NiH4 meanwhile accessible for hydrogen absorption/desorption. As a result, an extremely low activation energy (31.2 kJ mol –1 ) for the dehydrogenation reaction is achieved. This study provides alternative insights into designing nanosized MHs with both excellent hydrogen storage activity and thermal/mechanical stability exempting surface modification by agents. Abstract : Highly dispersed Mg2 NiH4 single‐crystal nanoparticles are in situ encapsulated into an ultrathin MgO layer via a gas–solid‐based methodology. Unexpectedly, such a thin passive film is demonstrated to possess superior gas‐selective permeability and be of particular importance in protecting the underlying active substance from further poisoning, sintering, or aggregating.